2009
DOI: 10.1007/s11664-009-0763-x
|View full text |Cite
|
Sign up to set email alerts
|

AFM Characterization of Raman Laser-Induced Damage on CdZnTe Crystal Surfaces

Abstract: IntroductionHigh quality CdZnTe (or CZT) crystals have the potential for use in room temperature gamma-ray and X-ray spectrometers. 1, 2 Over the last decade, the methods for growing high quality CZT have improved the quality of the produced crystals however there are material features that can influence the performance of these materials as radiation detectors. The presence of structural heterogeneities within the crystals, such as twinning, pipes, grain boundaries (polycrystallinity), and secondary phases (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 30 publications
2
12
1
Order By: Relevance
“…We assume that the appearance of the strong Te-related modes is caused by local heating of the sample surface, as this was shown in [75,77,78]. This assumption was confirmed by RS measurement using 633 nm excitation wavelength.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 72%
See 1 more Smart Citation
“…We assume that the appearance of the strong Te-related modes is caused by local heating of the sample surface, as this was shown in [75,77,78]. This assumption was confirmed by RS measurement using 633 nm excitation wavelength.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 72%
“…In this case, the penetration depth of the green wavelength radiation for CdTe and ZnTe is only 200 and 400 nm, respectively [75]. Thus, the excitation light is absorbed in a thin near-surface layer that could lead to local heating of the material followed by Te enrichment on the surface, even at low green laser excitation power [75,77,78]. In order to determine the position of Te-related modes, the tellurium crystal was measured as a reference, using three available laser excitations wavelengths.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 96%
“…As a result, this observation might be suggest that the ZnTe bonding was broken due to the highly focused laser which causes a localized surface heating effect and the free Te atoms migrate to the heated areas. Lucile C. Teague et al [42] had been used AFM and Raman to study the localized surface damage in the areas exposed to the Raman laser beam on Cd 1-x Zn x Te crystal surface with x=0.10. They found that (1) localized surface heating causes Cd material to be evaporated from the surface, which in some cases causes voids in the surface, and (2) free Te atoms are migrating to these heated areas.…”
Section: Raman Scatteringmentioning
confidence: 99%
“…[7] More information on these crystals has been published elsewhere. [5,8,12,13] The surfaces of each crystal were mechanically polished using standard techniques, with a final 0.05 µm alumina polish. Gold (Au) contacts were sputtered onto the as-polished crystal and the bulk currents were measured at room temperature as described below.…”
Section: Methodsmentioning
confidence: 99%